Increased Expression of HYAL1 in Pancreatic Ductal Adenocarcinoma. Issue 10 (November 2016) - Kohi, Shiro; Sato, Norihiro; Cheng, Xiao-Bo; Koga, Atsuhiro; Hirata, Keiji
Abstract : Objectives: Increased production and processing (degradation) of hyaluronan (HA) is critical for cancer invasion and metastasis. Although HA is known to be overexpressed in pancreatic ductal adenocarcinoma (PDAC), little is known about the expression and biological significance of HA-degrading enzymes, hyaluronidases (HYALs), in PDAC. Methods: Expression of HYALs mRNA was examined in PDAC cells by quantitative real-time RT-PCR. HYAL1 protein expression was examined in primary PDAC tumors by enzyme-linked immuno-sorbent assay. The migratory ability of PDAC cells was determined by a transwell cell migration assay. Results: Screening of mRNA expression of three major HYAL genes ( HYAL1, 2, and 3 ) identified HYAL1 as a gene overexpressed in PDAC cells. Treatment of PDAC cells with 5-aza-2′-deoxycytidine and/or trichostatin A further increased the HYAL1 expression, suggesting a possible involvement of epigenetic mechanisms in the transcriptional regulation of this gene. HYAL1 protein concentrations were significantly higher in primary PDAC tissues as compared with nontumor pancreatic tissues ( P = 0.049). Importantly, inhibition of HYAL activity by dextran sulfate significantly inhibited the migration of PDAC cells showing strong HYAL1 expression ( P = 0.002). Conclusions: These findings suggest that overexpression of HYAL1 is a common mechanism that may contribute to the aggressive phenotype of PDAC.